Healthcare and Big Data Digital Specters and Phantom Objects - Ebeling, Mary F.E.; SpringerLink (Online service) (New York : Palgrave Macmillan US(Imprint), 2016)
This highly original book is an ethnographic noir of how Big Data profits from patient private health information. The book follows personal health data as it is collected from inside healthcare and beyond to create patient consumer profiles that are sold to marketers. Primarily told through a first-person noir narrative, Ebeling as a sociologist-hard-boiled-detective, investigates Big Data and the trade in private health information by examining the information networks that patient data traverses. The noir narrative reveals the processes that the data broker industry uses to create data commodities-data phantoms or the marketing profiles of patients that are bought by advertisers to directly market to consumers. Healthcare and Big Data considers the implications these "data phantoms" have for patient privacy as well as the very real harm that they can cause.
Keywords: Big data; Human body-Social aspects